2016
DOI: 10.1038/bjc.2016.214
|View full text |Cite
|
Sign up to set email alerts
|

Endosialin expression in soft tissue sarcoma as a potential marker of undifferentiated mesenchymal cells

Abstract: Background:Soft tissue sarcomas are a group of neoplasms with differentiation towards mesenchymal tissue, many of which are aggressive and chemotherapy resistant. Histology and immunoprofiles often overlap with neoplasms of other lineages, and establishing an accurate histopathological diagnosis is crucial for correct management, and therapeutic stratification. The endosialin cell surface glycoprotein is predominantly expressed by stromal fibroblasts and pericytes in epithelial neoplasms; however, tumour cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
2
22
0
1
Order By: Relevance
“…Consequently, endosialin was considered a potential therapeutic target in sarcomas. Other studies confirmed these findings …”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…Consequently, endosialin was considered a potential therapeutic target in sarcomas. Other studies confirmed these findings …”
Section: Introductionsupporting
confidence: 70%
“…Other studies confirmed these findings. 6 Cancer July 15, 2019 Ontuxizumab is a humanized immunoglobulin G1κ antibody directed against endosialin and the first of this class to undergo clinical evaluation. Nonclinical pharmacological studies have shown that ontuxizumab has the ability to interfere with specific endosialin receptorligand interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has been shown that the presence of endosialin is essential for the cellular growth and the migration of pericytes, which are key regulators of tumor neoangiogenesis [18,19]. Interestingly, in some tumors, namely sarcoma and neuroblastoma, the expression of endosialin/TEM1 is not only limited to the tumor stroma and neovasculature but it is also present on tumor cell surface [11,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The B6FS cell line originates from a poorly differentiated fibrosarcoma ( 40 ). In poorly differentiated tumors, cancer cells are characterized by scant phenotypic similarity with cells of origin, mild pleomorphism, as well as intense mitotic activity ( 55 , 56 ). It is noteworthy that fibrosarcoma is a particularly heterogeneous tumor type, taking into account morphology, differentiation and behavior ( 57 ).…”
Section: Discussionmentioning
confidence: 99%